PENGARUH KUALITAS, CITRA INSTITUSI DAN BIAYA TERHADAP KEPUTUSAN MEMILIH KULIAH DI UNIVERSITAS SWASTA DI SUMBAWA - Abdul Salam; Nanda Febriani (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2024)
Private universities in Sumbawa play an important role in cultivating talent and driving social and economic change. This condition leads private universities in Sumbawa to exert a strong influence arising from the university's image, institutional quality, and tuition fees to facilitate parents' and students' decisions to enter private universities in Sumbawa. The research aims to test and determine the influence of quality, university image, and costs on the decision to study at private universities in Sumbawa. With a population consisting of a sample of 90 people. The technique is by distributing questionnaires to respondents and answering all research statement items. The results of new students at private universities in Sumbawa show that quality, university image, and tuition fees have a significant influence on the decision to choose to study at a private university.